PEMBUATAN HIT RADIOLVIVIUNOASSAY (RIA) MIKROALBUMINURIA DENGAN METODE COATED TUBE : PERBANDINGAN TABLING POLISTIREN "PLAIN" DAN "DASAR BINTANG" - V. Yulianti Susilo; Sutari Sutari (Widyariset, 2009)
Microalbuminuria is a physiological condition ofp atient in which albumin is excreted in urine at 20-200 pg/min or 30-300 mg/day. Determination of microalbumin content in the patient urine is very important for early detection ofmicroalbuminuria before nephropathy occurred. Detection ofrnicroalburnin in the urine is commonly performed by radioimmunoassay (R1A) technique. Human serum albumin labeled with 1251 is commonly used as a tracer and bound and unbound phases in the reaction mixture that can be separated easily and quickly with a coated tube method. Production of R1A kit of microalbuminuria  involves preparation of antibody coated into two solid phases of polystyrene tube plain and polystyrene bottom star tube, HSA-'251 tracer and standard solution. The polyclonal anti-human serum albumin (anti-HSA)  generated in the rabbit with titer 1 : 15000 was obtained after one year then was coated into polystyrene tubes, the tracer HSA-'251 was prepared using an iodogen method. Series of HSA standard were made by dilution of HSA with synthetic urine.  The yield of HSA-121 tracer was about 83,94% with radiochemical purity of 92% and specific activity of 3,3576 pCi/pg. The microalbuminuria RIA kit shows good assay performance of 1, 05% NSB (Non Spesific Binding) and 78,6% B/T The polystyrene bottom star tube shows more higher BIT of bound and could be maintained within 70 days.